Kinetically Favorable Vapor–Adsorbate–Solid Growth of Rutile Nanowires. Issue 7 (14th May 2019) - Xie, Dong Yue; Lin, Ming‐hui; Zhou, Wei; Wang, Jian; Zhu, Guo‐zhen
Abstract: The vapor‐based synthesis of nanowires, particularly vapor–liquid–solid growth and its variants, is an undoubtedly promising method for fabricating high‐quality silicon‐based and group III–V semiconductors. However, the assembly of oxide nanowires has limited success while adopting these methods. Herein, a simple and scalable approach is developed to synthesize single‐crystal oxide nanowires with controllable morphology. Using titanium oxide as the model system for validation, this approach emphasizes the essential role of the surface characteristic of the seed for the space‐confined growth of nanowires. The shape and growth directions of nanowires can be additionally tailored by using bimetallic seeds, with compositional segregations and dissimilar surface characteristics. Since the source material has the same thermodynamic conditions as the produced nanowires within a closed vessel, the results suggest that the growth of nanowires can be dominated by the kinetic enrichment at seed surfaces or referred to as kinetically favorable vapor–adsorbate–solid growth. While identifying the key thermodynamic and kinetic parameters during growth, this approach is applicable for a wide range of materials. Abstract : A simple, controllable, and scalable approach to synthesize single‐crystal oxide nanowires with uniform morphology, during which oxide vaporizes, adsorbs at the seed surface, and then grows into nanowires, is demonstrated. The shape and growth direction can be tuned by manipulating the surface characteristics of the seed particles. This approach is distinct with traditional vapor‐based synthesis.